Psychological Influence of Self-Management on Exercise Self-Confidence, Satisfaction, and Commitment of Martial Arts Practitioners in Korea: A Meta-Analytic Approach - Kim, Hyun-Duck; Cruz, Angelita Bautista (Frontiers in Psychology, 2021)
This study aimed to meta-analyse the relationship between self-management and exercise self-confidence, satisfaction, and commitment in both modern and traditional martial arts among Korean practitioners. We examined the level of sports participation and different martial arts sports as potential moderating variables. In total, 22 studies yielded 299 individual effect sizes and were included in the final meta-analytic pool. The analyses revealed a moderate effect of self-management on exercise satisfaction and self-confidence; and a large effect self-management on exercise commitment. Especially, the effect of the training dimension of self-management was large on exercise commitment and satisfaction, while that of the mental dimension was large on exercise self-confidence. The effects of self-management on exercise satisfaction, commitment, and self-confidence were large in judo, Ssireum, and wrestling, respectively. Finally, the use of self-management was relatively more effective for non-elite participants than for elite practitioners. Our results highlight the effectiveness of self-management to enhance Korean martial arts practitioners’ exercise self-confidence, commitment, and satisfaction, findings that may potentially be extended internationally and to other types of sports; further, they showcase the importance of the promotion of interventions and educational programs on how to incorporate/employ self-management in athletes’ sports training.